Review Nilai Perusahaan Tambang di Indonesia dari Sudut Pandang Green Accounting dan CSR - Sari, Anggi Nofita; Oktavia, Reni; Widiyanti, Ade (Penerbit Goodwood, 2024)
Purpose: This study aims to determine the effect of green accounting and Corporate Social Responsibility (CSR) on company value in mining companies. Research methodology: The population in this study comprises mining companies listed on the IDX during the period 2018-2023. Purposive sampling was used with a sample of 16 mining companies in Indonesia. Furthermore, this study used multiple linear regression analysis with the SPSS 25 software. Results: The results indicate that green accounting does not affect company value. However, Corporate Social Responsibility (CSR) influences company value in mining companies. Limitations: This study covers the Covid-19 pandemic period (2019 and 2020), during which a number of companies experienced less stable conditions. Under these conditions, it causes company performance to fluctuate and has a very varied range of values between companies. This makes the research data slightly different, which requires more in-depth analysis. Contribution: This study can serve as a reference and contribute to the benefits of the academic community and managerial parties within mining companies.